(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2018)
At the beginning of higher education, many students find it difficult to maintain an adequate pace of study, differentiate between their initial expectations and the reality of their chosen program, and find meaning in university studies, as these young people are unable to relate this stage to their life plans. It should be noted that this whole situation can encourage students to reflect on whether the program they have chosen is the right one or even whether studying for a degree is what they really want to do. This could be due to a lack of preparation for entering university, a lack of knowledge or distortion of information about the profile of the chosen degree, or difficulty adapting to the new university life, which can put students in a situation of academic and psychosocial vulnerability.